Acoustic Performance of Mixing EFB and OPF Low-Density Fibreboards in Different Thickness - Chandran M.R.; Sheng E.L.; Nasir M.N.; Kean Y.W.; Ibrahim Z. (Springer Science and Business Media B.V., 2023)
Fast growth of worldwide oil palm industry and nations economics have affected the environment for the mishandling of oil palm waste, which has endangered the flora and fauna that surrounds it. The wastes of oil palm can be turned into good source of material for sound absorption or other usages. Furthermore, the awareness about the harmful effects of fibreglass as sound absorbing material has certainly increased and the demand of replacing it with natural fibres are growing day by day. This research highlights the acoustic properties of mixing empty fruit bunch (EFB) and oil palm frond (OPF) at mixing ratios of 50% EFB-50% OPF, 40% EFB-60% OPF, 30% EFB-70% OPF and 20% EFB-80% OPF in thickness of 12, 14, 16 and 18mm with density of 120kg/m3. The sound absorption coefficient, SAC (?) test was conducted using the impedance tube method (ITM) and the morphology of the samples were examined using scanning electron microscope, SEM. The results showed no trend for the sac values with increasing of thickness and OPF contents. Nevertheless, it is noteworthy that the frequency range with 0.8 sac values and above are increased with thickness, it may be attributed to tortuosity effects. The morphology of EFB and OPF mixture may play a crucial role in determining the sound absorption. 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.